An Opinion on Promises, Threats, and Accusations In the 2022 Russo-Ukrainian War - Bergstra, Jan Aldert (Transmathematica, 2022)
Promise Theory is used as a framework for analysing the baffling escalation in the third phase of the Russo-Ukrainian war that started on February 24, 2022. It is argued that an exit of the UK from NATO may constitute an important step towards a more reliable and functional security architecture in Europe.